Avaliação do desempenho dos meios filtrantes de celulose RAD + e RAD Plus submetidos à filtração de gases a altas pressões - Lima, Bruno de Araújo (2015)
The gas filtration process has several advantages, such as to prevent damage to the environment and health of living beings and to avoid damage in the equipment used in various industrial processes. The filter media applied in these processes can be made of various materials, including metal, fiberglass, polypropylene, polyester and cellulose, with the latter being highlighted by its low cost. The objective of this study is to evaluate the performance of the cellulose filters RAD + and RAD Plus, through permeability, filtration and porosity of the filter cake tests, when subjected to high pressures using the experimental apparatus located in the Environmental Control Laboratory in the Chemical Engineering Department at UFSCar and talc as particulate matter. The working conditions used in the experiments were pressures of 93, 193, 293, 393 and 493kPa, for the permeability tests, and 93, 293 and 493kPa, for the filtration tests. In the permeability tests, the superficial velocity of the gas was varied from 0 to 0.25m/s, while in the filtration tests, the velocities of filtration were 0.05 and 0.06 m/s. The porosity of the cake filtration was determined by mathematics correlations. The permeability constants calculated for both filter media could be considered constant with pressure. For filtration assays, it could be observed that increasing the pressure of the system was the mass withheld by filter media increased for the same pressure drop, without any significant variation with the filtration velocities studied. It was also observed an increase in porosity and a decrease in the resistance of cake filtration when the system pressure was raised.